The assessment of locally thinned areas: Background to the guidance given in Annex G of BS 7910:2013. (January 2019) - Cosham, Andrew; Andrews, Robert
Abstract: Annex G The assessment of corrosion in pipes and pressure vessels in the then BS 7910:2005 has been, in BS 7910:2013, renamed Assessment of locally thinned areas (LTAs) and substantially expanded to cover geometries other than straight pipes, e.g. elbows and spheres. An outline of the origins of Annex G, and how and why it has been expanded is given. A comparison with full-scale burst tests of pipes or vessels containing LTAs subject to internal pressure is presented. Highlights: Annex G Assessment of locally thinned areas (LTAs) has been expanded to cover geometries other than straight pipes. An outline of the origins of Annex G, and how and why it has been expanded is given. A comparison with full-scale burst tests of pipes or vessels containing LTAs subject to internal pressure is presented.